Quantization-based integration methods for delay-differential equations - Castro, Rodrigo Daniel (2011)
This paper introduces a new class of numerical delay differential equation solvers based on state quantization instead of time slicing. The numerical properties of these algorithms, i.e., stability and convergence, are discussed, and a number of benchmark problems are being simulated and compared with the state-of-the-art solutions to these problems as they have been previously reported in the open literature.